LITTLE DOCTOR VIRTUAL TRAINING WITH SNOWBALL TECHNIQUE IN PANDEMIC COVID-19 ERA IN ELEMENTARY SCHOOL MALANG - Merlya Balbeid; Dyah Nawang Palupi Pratamawari; Khusnul Munika Listari; Zefry Zainal Abidin; Trias Arlis Subekti; Renita Rahma Chairu Nisa (Caring : Jurnal Pengabdian Masyarakat, 2022)
Strategies that can be taken to achieve caries-free Indonesia 2030 include is increasing promotive and preventive efforts for dental and oral health services. Even in this Pandemic Covid 19 the delivery of counseling or promotive materials is not done face-to-face, because it avoids the risk of local transmission Covid-19 virus. This study aims to increase the knowledge of dental and oral health of elementary school students during the pandemic. The method was through audiovisual media facilitated with online meeting zoom and e-Book. This activity was carried out using the snow-ball technique, 6 elementary schools doing this activity. The activity started with dental training by the FKGUB team through the media zoom with room separation in 6 breakout rooms, so a total of 42 participants attended. After that were held for Little Doctors activities to educate 5 friends in their elementary schools, so there was 150 participants. In the pre-test results, as many as 18 students scored below 50 and as many as 10 students scored above 50. In the post-test results, 24 students got scores above 50 and 1 student got a score of 20. There is a difference knowledge level oral health of students by little doctor with online education in pandemic Covid-19 Era in elementary school Malang.